2022
DOI: 10.1016/j.jjcc.2021.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of serum lactate dehydrogenase on the short-term prognosis of COVID-19 with pre-existing cardiovascular diseases

Abstract: Background Patients with coronavirus disease 2019 (COVID-19) and underlying cardiovascular comorbidities have poor prognoses. Our aim was to identify the impact of serum lactate dehydrogenase (LDH), which is associated with mortality in acute respiratory distress syndrome, on the prognoses of patients with COVID-19 and underlying cardiovascular comorbidities. Methods Among 1,518 patients hospitalized with COVID-19 enrolled in the CLAVIS-COVID (Clinical Outcomes of COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Similar to other studies, we found age ( 21 ), male gender ( 28 ), and underlying chronically illness ( 29 ) were risk factors of in-hospital mortality of patients with COVID-19. Our study also found that D-dimer, representing thrombotic risk ( 30 ), and LDH, representing systemic inflammation ( 31 ), were also associated with prognosis in multivariable logistic regression analysis. These results suggest that age, sex, underlying chronically illness, D-dimer, and LDH deserve further study.…”
Section: Discussionsupporting
confidence: 66%
“…Similar to other studies, we found age ( 21 ), male gender ( 28 ), and underlying chronically illness ( 29 ) were risk factors of in-hospital mortality of patients with COVID-19. Our study also found that D-dimer, representing thrombotic risk ( 30 ), and LDH, representing systemic inflammation ( 31 ), were also associated with prognosis in multivariable logistic regression analysis. These results suggest that age, sex, underlying chronically illness, D-dimer, and LDH deserve further study.…”
Section: Discussionsupporting
confidence: 66%
“…Since it reflected cardiomyocyte necrosis, LDH was historically used to diagnose myocardial infarction [12,29]. Additionally, LDH is a generic sign of acute or chronic tissue injury and is considered an inflammatory marker [30]. Infection with COVID-19, chronic obstructive pulmonary disease, acute lung injury, and pulmonary embolism have been reported to be associated with elevated blood LDH levels [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, LDH is a generic sign of acute or chronic tissue injury and is considered an inflammatory marker [30]. Infection with COVID-19, chronic obstructive pulmonary disease, acute lung injury, and pulmonary embolism have been reported to be associated with elevated blood LDH levels [30][31][32]. Previous research has shown that LDH was not only associated with activating certain proto-oncogenes but also played a critical role in the maintenance of tumor invasiveness, metastatic potential, chemoresistance, and radioresistance [6,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…In a pooled analysis by Henry et al containing nine studies with 1532 patients, it was found that elevated LDH values were associated with a sixfold increased risk of developing severe COVID-19 and a 16-fold increase in mortality rate [ 56 ]. According to Masumoto et al, serum LDH values > 355U/L at admission were associated with an increased risk of death in patients with COVID-19 and cardiac comorbidities [ 57 ].…”
Section: Discussionmentioning
confidence: 99%